ANALISIS PEMBELAJARAN BIOLOGI SMA/MA DI JABODETABEK DITINJAU DARI STANDAR PROSES - Fadlilah, Dina Rahma; Herlanti, Yanti (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
A good implementation of Process Standard is a part of the effort to improve the quality of learning process. In Permendikbudristek No. 16 of 2022 regarding Process Standard, it is stated that learning is done in an interactive, inspiring, enjoyable, challenging and motivating environment for students. This type of learning had actually been initiated in the 2013 Curriculum through a scientific approach which proposes several learning models, namely discovery/inquiry learning and problem-based learning; such as problem-based learning (PBL) and project-based learning (PjBL). Therefore, this study aims to analyze the scientific approach in Biology learning as an implementation of Process Standard in Jakartan High Schools. Furthermore, this study used quantitative and qualitative methods as its approach. It found that teachers had implemented the scientific approach in their classrooms. However, results from students' perceptions showed the opposite. They stated that teachers did not effectively do “hands-on” activities through discovery/inquiry and PjBL. Moreover, this study suggests that the implementation of the Process Standard that have been effectively applied since the 2013 Curriculum needs to be maintained in Kurikulum Merdeka (in English: Emancipated Curriculum) because it is still relevant with the goals of Emancipated Curriculum. Finally, the findings of this study should be addressed so it can improve the implementation of Process Standard in the Emancipated Curriculum.